2023
DOI: 10.3389/fendo.2023.1116864
|View full text |Cite
|
Sign up to set email alerts
|

Continuous glucose monitoring for children with hypoglycaemia: Evidence in 2023

Abstract: In 2023, childhood hypoglycaemia remains a major public health problem and significant risk factor for consequent adverse neurodevelopment. Irrespective of the underlying cause, key elements of clinical management include the detection, prediction and prevention of episodes of hypoglycaemia. These tasks are increasingly served by Continuous Glucose Monitoring (CGM) devices that measure subcutaneous glucose at near-continuous frequency. While the use of CGM in type 1 diabetes is well established, the evidence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Another report from a GSDIb patient with bowel disease treated with G-CSF and continuous gastric deep feeding showed events of asymptomatic mild hypoglycemia < 3.3 mmol/L (range 2.6-3.3) measured by flash glucose monitoring during the first week of treatment and promptly corrected by oral glucose administration (24). Notably, accuracy of CGM devices in the hypoglycemia range is low and hypoglycemic events should be always verified by glucometer (114)(115)(116). However, time below range (TBR) decreased and time in range (TIR) increased also after oral refeeding.…”
Section: Empagliflozin Use In Glycogen Storage Disease Type Ibmentioning
confidence: 99%
“…Another report from a GSDIb patient with bowel disease treated with G-CSF and continuous gastric deep feeding showed events of asymptomatic mild hypoglycemia < 3.3 mmol/L (range 2.6-3.3) measured by flash glucose monitoring during the first week of treatment and promptly corrected by oral glucose administration (24). Notably, accuracy of CGM devices in the hypoglycemia range is low and hypoglycemic events should be always verified by glucometer (114)(115)(116). However, time below range (TBR) decreased and time in range (TIR) increased also after oral refeeding.…”
Section: Empagliflozin Use In Glycogen Storage Disease Type Ibmentioning
confidence: 99%
“…In a recent review by Worth et al. on the use of CGM, they found that hypoglycaemia sensitivity reduces as the threshold for hypoglycaemia decreases ( 61 ). The lowest hypoglycaemia sensitivity was reported at 17% with a hypoglycaemia threshold of 2.6mmol/L ( 62 ), as opposed to the highest hypoglycaemia sensitivity of only 86% with a hypoglycaemia threshold of 3.9mmol/L ( 63 ).…”
Section: Hypoglycaemia In Adrenal Insufficiencymentioning
confidence: 99%
“…However, unlike diabetes, evidence for use in CHI is scant (60-62). Accuracy is lower than that of glucometer testing and any hypoglycaemia detected by a CGM device must be verified with a point of care glucometer before treatment is administered (62,63). In hospital, CGM can be used to provide reassurance about normoglycaemia and thus reduce the number of point of care glucose tests (64).…”
Section: Continuous Glucose Monitoring Cgm In the Hospital Settingmentioning
confidence: 99%